2022
DOI: 10.3390/plants11091160
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Patterns of Invasive Buffelgrass (Cenchrus ciliaris) in Mexico Estimated with Climate Niche Models under the Current and Future Climate

Abstract: In Mexico, buffelgrass (Cenchrus ciliaris) was introduced in the middle of the 20th century. Currently, buffelgrass has become an invasive species and has colonized various ecosystems in the country. In addition to its invasive capacity, climate change is a factor that has to be taken into account when considering how to effectively manage and control this species. The climatic niche models (CNM) and their projections for climate change scenarios allow for estimating the extent of biological invasions. Our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
1
3
0
2
Order By: Relevance
“…In this study, the total trend in suitable areas for L. temulentum increased from the current climate to future scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in the 2030s and 2050s. This result is similar to other studies on the potential geographical distribution of non-invasive plants; for example, suitable areas of Cenchrus ciliaris increased under SSP1-2.6 and SSP2-4.5-2050s, and for Spartina anglica the suitable areas increase under SSP5-8.5-2100 in Northern Europe ( Borges et al., 2021 ; Siller-Clavel et al., 2022 ). IPCC has indicated that global warming is likely to increase by 1.5 °C from 2030 to 2052 at the current rate ( IPCC, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the total trend in suitable areas for L. temulentum increased from the current climate to future scenarios (SSP1-2.6, SSP2-4.5, and SSP5-8.5) in the 2030s and 2050s. This result is similar to other studies on the potential geographical distribution of non-invasive plants; for example, suitable areas of Cenchrus ciliaris increased under SSP1-2.6 and SSP2-4.5-2050s, and for Spartina anglica the suitable areas increase under SSP5-8.5-2100 in Northern Europe ( Borges et al., 2021 ; Siller-Clavel et al., 2022 ). IPCC has indicated that global warming is likely to increase by 1.5 °C from 2030 to 2052 at the current rate ( IPCC, 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…La especie C. ciliaris tuvo presencia importante en la vegetación de gramíneas observada en el agostadero evaluado, ya que representó el 57 % del número total (n=745) de individuos colectados y su biomasa, calculada tomando en cuenta el número de individuos y el peso promedio de los individuos de la especie mostrados en el Cuadro 1, representó el 80 % de la biomasa registrada en el agostadero evaluado. En las áreas evaluadas en el presente estudio, el pasto C. ciliaris presente se estableció por dispersión natural, dejando en evidencia su alto potencial para establecerse en los agostaderos en México (31) . La especie nativa con mayor presencia en el presente estudio fue Pappophorum bicolor, que tuvo registro de 125 individuos, es decir el 17 % del total, cuya biomasa representó solo 11 % de la biomasa total (Cuadro 1).…”
Section: Discussionunclassified
“…Because of these physiognomy traits, these species are valuable native forage plants and have desirable qualities for use on degraded rangelands of these desert regions. In contrast, both species and particularly C. ciliaris have been introduced to different desert regions such as Western Australia [37] , northwestern Mexico and the southwestern United States [27,38] as forage plants and for their fodder value. However, it has been reported that C. ciliaris has spread from forage grasslands to adjacent natural desert habitats and invaded native plant communities [39][40][41] .…”
Section: Discussionmentioning
confidence: 99%